Review of the clinical activity of medical microbiologists in a teaching hospital. - Wooster, S L (1999)
BACKGROUND: The clinical interactive role of medical microbiologists has been underestimated and the discipline is perceived as being confined to the laboratory. Previous studies have shown that most microbiology interaction takes place over the telephone. AIM: To determine the proportion of clinical ward based and laboratory based telephone interactions and specialties using a microbiology service. METHODS: Clinical microbiology activity that took place during November 1996 was prospectively analysed to determine the distribution of interactions and specialties using the service. RESULTS: In all, 1177 interactions were recorded, of which nearly one third (29%) took place at the bedside and 23% took place on call. Interactions involving the intensive treatment unit, general ward visits, and communication of positive blood cultures and antibiotic assays were the main areas of activity identified. There were 147 visits to 86 patients on the general wards during the study, with the number of visits to each individual varying from one to eight. The need for repeated visits reflected the severity of the underlying condition of the patients. Ward visits were regarded as essential to obtain missing clinical information, to assess response to treatment, and to make an appropriate entry in a patient's notes. CONCLUSIONS: Ward visits comprise a significant proportion of clinical microbiology interactions and have potential benefits for patient management, service utilisation, and education.